Manajemen Pendidikan Kesetaraan Kejar Paekt C Pusat Kegiatan Belajar Masyarakat (PKBM) Permata Mandailing Natal - Somed Lubis; Akrim Akrim; Indra Prasetia (Jurnal Manajemen Pendidikan Dasar, Menengah dan Tinggi [JMP-DMT], 2023)
The type of research used in this research is qualitative research with descriptive research type. The data and information needed in this study were obtained from information from informants, namely people who were considered to know and could be trusted in providing accurate information using two types of data, namely primary data and secondary data. Data collection techniques in this research were direct observation at the research location, in-depth interviews and documentation at the research location. The results of the research show that the implementation of the four management functions of the community learning activity center when viewed from the planning function at PKBM Permata has been going well. It can be seen that PKBM planning is going according to the planning that has been done. the organization at PKBM Permata has been going well. It can be argued that the center of community learning activities should hold deliberations before holding learning activities in the fields involved in learning activities in order to achieve goals according to the vision and mission. the implementation of PKBM Permata has been going well. It can be argued that the process of carrying out learning can be done anywhere because it does not have to be in the room and the implementation of learning activities is scheduled on Saturdays and Sundays. supervision at PKBM Permata is categorized as good because those who carry out each supervision need a report which is reported at any time to the Mandailing Natal District Education Office